TINJAUAN PENJADWALAN WAKTU DAN TENGA KERJA PADA PEKERJAAN REHABILITASI DAN REKONSTRUKSI BERAT JEMBATAN SOKLAT - Rachman, Ari Putra; Djafar, Fazrin (Universitas Bina Taruna Gorontalo, 2022)
Projects in the construction industry are temporary activities that last for a limited period of time, with certain resource allocations and aim to carry out tasks whose targets have been clearly outlined. In connection with this, a project planning method is needed which is expected to coordinate various activities in a job so that the project can be completed within the specified timeframe. The purpose of this research is to plan the most appropriate time, optimize the use of labor for each work item and find out the obstacles faced in the implementation of the Soklat Bridge Heavy Rehabilitation & Reconstruction project. The method that can be used in overcoming problems in time and manpower planning is to use the Crash Program, and use CPM (critical path method) or commonly known as Network Planning Diagram. This method is made to get the normal project life and the critical path that clarifies what activities will be shortened. From the results of the crash program experiment for 3 (three) times, the shortest work duration was 220 calendar days, namely the 3rd crash program.